New acquisitions from the Hellenistic-Roman-Byzantine east necropolis of Hierapolis in Phrygia: the unguentaria - Cappelletto, Erika; Indgjerd , Hallvard (Rei Cretariae Romanae Fautorum Acta, 2017)
Since 2007 the University of Oslo has conducted investigations in the East Necropolis of Hierapolis (Hierapolis Necropolis Est-HNE in the context of the Thanatos project) in collaboration with the Italian archaeological mission, MAIER. The project encompasses not only the excavations of interesting areas but also a geographical survey as exhaustive recording of the structures in this area is lacking. The excavations have uncovered a wide range of objects in ceramic, glass and metal.